2017
DOI: 10.1002/1873-3468.12599
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CRISPR/Cas9‐mediated biallelic genome targeting with dual surrogate reporter‐integrated donors

Abstract: The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) system has recently emerged as a simple, yet powerful genome engineering tool, which has been widely used for genome modification in various organisms and cell types. However, screening biallelic genome-modified cells is often time-consuming and technically challenging. In this study, we incorporated two different surrogate reporter cassettes into paired donor plasmids, which were used as both the surrogate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Lentiviral or plasmid delivery of Cas9 and sgRNA often utilizes a selection gene encoding either a drug selectable marker (hygromycin, blasticidin, puromycin, …) or a reporter protein (GFP, NGFR, …) to isolate cells that are successfully transduced or transfected. When RNPs are transfected or electroporated, alternative strategies can be used such as surrogate reporters (Ramakrishna et al, 2014b, He et al, 2016Wu et al, 2017). However, these methods are inefficient for assessing sgRNAs efficiency at a large scale because it is both time-and labour-consuming to construct a specific reporter for each individual sgRNA.…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Lentiviral or plasmid delivery of Cas9 and sgRNA often utilizes a selection gene encoding either a drug selectable marker (hygromycin, blasticidin, puromycin, …) or a reporter protein (GFP, NGFR, …) to isolate cells that are successfully transduced or transfected. When RNPs are transfected or electroporated, alternative strategies can be used such as surrogate reporters (Ramakrishna et al, 2014b, He et al, 2016Wu et al, 2017). However, these methods are inefficient for assessing sgRNAs efficiency at a large scale because it is both time-and labour-consuming to construct a specific reporter for each individual sgRNA.…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Particularly, integration of transgenes into the genome relying on HDR-mediated integration (“knock in”) is an inefficient process suffering from low editing rates compared to gene disruptions mediated by NHEJ (“knock out”). HDR-mediated site-specific integration can in some scenarios be achieved with high efficiency in cell types and loci particularly permissive to gene editing [ 7 ], but is generally restricted to < 30% of cells obtaining a targeted integration in most cases [ 8 10 ]. Furthermore, HDR activity is largely restricted to the S and G2 mitotic phases of the cell cycle, where homologous sister chromatids are present for natural DNA repair.…”
Section: The Bottlenecks Of Genome Editingmentioning
confidence: 99%
“…A dual surrogate reporter system containing two different reporter cassettes was designed to also act as repair template for HDR, thereby potentially allowing enrichment of both INDELs and integration events. One reporter cassette can function as surrogate reporter for nuclease-activity and enrichment and the second reporter for knock-in and screening of biallelically targeted cells based on dual antibiotic selection yielding 6.7-fold enrichment (from 2.70 to 18.18%) of biallelic integrations compared to the use of only one reporter [ 8 ]. Comparison of NHEJ- and SSA-based surrogate reporter systems in one study revealed superior enrichment when utilizing an SSA-based surrogate reporter system achieving up to 34.8-fold enrichment (from 2.1 to 72.7%) of INDELs compared to non-selected cells with an optimal DR length of 200 bp [ 103 ].…”
Section: Enrichment Of Nuclease-active Cells Using Exogenous Surrogat...mentioning
confidence: 99%
“…One strategy relies on sequential targeting of each allele of the gene-of-interest and inserting expression cassettes for different fluorescent proteins at the mutation sites by way of homology directed repair (HDR). This will allow cells with both alleles mutated to be positively selected with FACS [4]. Similarly, other HDR based targeting methods have been developed to insert positive selection markers including drug resistance gene and fluorescent markers to the targeted loci and have achieved varying degree of success [5,6].…”
Section: Introductionmentioning
confidence: 99%